Optimasi Pemilihan Pekerja Bangunan Proyek Pada PT. Citra Anggun Pratama Menggunakan Algoritma Genetika - Arviananda Bahtiar; Wayan Firdaus Mahmudy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
PT. Citra Anggun Pratama is a company engaged in construction, one of their human resources are the builders. Problems often encountered in the company is the incompatibility of builder election to the needs of corporate projects that resulted in disruption of the project. Genetic algorithm is one type of Evolutionary Algorithms (EAs) are the most popular and commonly used because of their ability to solve various complex problems, so it can be applied to find optimal solutions to the problems of election workers. Process of finding solutions in this study begins with the generation of chromosome accommodated in the population, then carried the crossover and mutation rate to get the new generation then be selected to get the best solution. Based on test results obtained best results on the population size of 420, 150 iterations, combination of Mr 0.5 and Cr 0.5 which is optimal or near-optimal results. The result is a recommendation in the way of the builder selection.